Analysis of Showme Store's Marketing Communication Strategy in Shaping Consumer Responses at Bintaro Jaya Xchange Mall 2 - Michelle Oktaviani; Fabianus Fensi (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The marketing communication strategy implemented by a store will impact the form of response shown by customers. This is because communication strategy is important to attract customer attention in making purchases. The purpose of this study is to analyze and describe the marketing communication strategy implemented by Showme Store in shaping consumer responses at Bintaro Jaya Xchange Mall 2. The theory used by the researcher is the elaboration likelihood model with central and peripheral paths. The object chosen in this study is Showme Store located at Bintaro Jaya Xchange Mall 2. The researcher used a qualitative approach by conducting interviews with 3 internal sources and 3 external sources. The study findings show that aspects of recommendation strategy, employee training, employee roles, upselling, affordable prices, use of social media, customer response, evaluation, service and purchase interest were found from the results of the answers given by the sources. In this case, Showme Store has provided training to employees who play an important role in representing Showme Store in front of customers. Not only that, the marketing communication strategy by providing recommendations, upselling and comfortable service is a consideration for customers to make purchases. The use of social media, including WhatsApp communities, helps Showme Store provide information about promotions running on specific days. Showme Store also conducts evaluations to ensure that undersold products can be resold to prevent dead stock. Recommendations for Showme Store's marketing communications strategy to shape consumer response include maintaining and improving service and implementing social media usage.